Wolbachia Associations with Insects: Winning or Losing Against a Master Manipulator - Correa, Claudia C.; Ballard, J. W. O. (Frontiers in Ecology and Evolution, 2016)
Wolbachia are intracellular, maternally inherited bacteria with an impressive history of adaptation to intracellular lifestyles. Instead of adapting to a single host lineage, Wolbachia evolved ways to jump across host species and establish relatively stable associations maintained through vertical transmission. Wolbachia are capable of manipulating the reproduction of infected hosts in a remarkable way. Traditionally, such reproductive manipulations have been regarded as the general mechanism by which Wolbachia spread through host populations. Recent evidence suggests that Wolbachia-host interactions are more complex than previously thought and may be driven by the onset and resolution of conflicts of interest. Here, we discuss how reproductive manipulation phenotypes may be transient. As the host adapts to infection, manipulation phenotypes attenuate and the continuity of the symbioses may rely on the physiological advantages Wolbachia may confer to their host. For facultative symbionts, such benefits are likely to be dependent on the environment. Here, we also review evidence that supports the view of environment-dependent facultative mutualism as a stable evolutionary outcome of Wolbachia infections beside extinction and obligate symbioses. Finally, our current understanding of the biology of mitochondria and Wolbachia unravels remarkable parallels in the way they interact with the nuclear genome. Great insights into both the Wolbachia and mitochondrial research fields can be revealed if such fields are considered to be overlapping, rather than independent from each other.